The Role of Leptin in Childhood Immune Thrombocytopenia (ITP): An Anti-Inflammatory Agent? - Thomas, Iason (Int J Mol Sci, 2021)
To investigate the effect of leptin in childhood ITP, we measured plasma leptin in 39 children with acute ITP, after treatment and in remission, and in 33 healthy age/BMI-matched controls. We also cultured ITP and control peripheral blood mononuclear cells (PBMCs) with recombinant leptin to assess its direct effect on pro/anti-inflammatory cytokine gene expression. A significant increase in leptin was observed in children with active disease compared to controls. A significant inverse correlation of leptin with platelet count was also observed in children with acute ITP. Leptin remained high after treatment with IVIg, whereas steroid treatment lowered leptin below control levels. In remission, leptin was in the control range. Cytokine gene expression was significantly increased in children with acute ITP compared with controls, with highest expression for IFN-γ and IL-10. IVIg/steroid treatment significantly decreased IFN-γ and IL-10 expression. In remission, IFN-γ and IL-10 expression remained low. Addition of leptin to PBMCs isolated from patients in remission resulted in a significant increase in IL-10 gene expression compared to controls. Further experiments with purified T-cells and monocytes identified monocytes as the source of leptin-induced IL-10. We suggest that leptin acts as an active anti-inflammatory agent in childhood ITP by promoting IL-10 secretion by monocytes.